How are witnessed workplace bullying and bystander roles related to perceived care quality, work engagement, and turnover intentions in the healthcare sector? A longitudinal study. (February 2023) - Holm, Kristoffer; Jönsson, Sandra; Muhonen, Tuija
Abstract: Background: Workplace bullying is widespread in the healthcare sector and the negative effects are well known. However, less attention has been paid to bystanders who witness bullying in the workplace. Bystanders can affect the bullying process by engaging in active, passive, or destructive behaviors. There is a need to study work-related and organizational consequences of witnessing bullying and bystander behaviors. Objective: The aim was to explore how witnessed workplace bullying and bystander behaviors are associated with work-related and organizational consequences, such as perceived quality of care, work engagement, and turnover intentions, among healthcare workers over time. Design: Longitudinal design. An online questionnaire was administered twice over the course of six months. Setting(s): Employees in the healthcare sector in Sweden, such as physicians, nurses, and assistant nurses, responded to the questionnaire. Participants: 1144 participants provided longitudinal data. Methods: Structural equation modeling was used to explore the associations between witnessed bullying, bystander behavior, work-related and organizational factors over time. Results: Witnessed workplace bullying ( B = − 0.18, 95 % CI [− 0.23 to − 0.12]) and the bystander outsider role ( B = − 0.24, 95 % CI [− 0.29 to − 0.19]) were statistically significantly related to a decrease in perceived quality of care. Work engagement was statistically significantly predicted by all three bystander roles over time; positively by the defender role ( B = 0.11, 95 % CI [0.05–0.17]), and negatively by the outsider role ( B = − 0.23, 95 % CI [− 0.29 to − 0.16]), and the assistant role ( B = − 0.32, 95 % CI [− 0.41 to − 0.24]). The outsider role ( B = 0.12, 95 % CI [0.02–0.22]), the assistant role ( B = 0.17, 95 % CI [0.03–0.30]), and witnessed workplace bullying ( B = 0.18, 95 % CI [0.08–0.29]), all positively predicted increased turnover intentions at a subsequent time point. Conclusions: In addition to the direct negative impact workplace bullying has on those targeted by it, witnessing bullying and taking different bystander roles can have work-related and organizational consequences by influencing perceived care quality, employees' work engagement, and their intention to leave the organization.